Near-fields for a circular loop antenna above a ground plane - Hamed, Sameir M. Ali; Bashir, Saad Osman (AES 2013, 2013)
Exact electromagnetic near-fields expressions of a circular loop antenna (CLA) over a ground plane are presented in this paper. The technique is based on the spherical Bessel functions (SBFs) and associated Legendre polynomials (ALPs) expansion for the Green's function. The known far-field expressions for the loop/ground plane problem are derived from the general expressions by applying the large argument approximations for SBFs. Fields of the uniform CLA on the axis of the loop are obtained as a special cases.